Asexual Epichloë Fungi—Obligate Mutualists - John R. Caradus; Stuart D. Card; Katrin G. Hewitt; David E. Hume; Linda J. Johnson (Encyclopedia, 2021)
Asexual Epichloë are obligate fungal mutualists that form symbiosis with many temperate grass species, providing several advantages to the host. These advantages include protection against vertebrate and invertebrate herbivores (i.e., grazing livestock and invertebrate pests, respectively), improved resistance to phytopathogens, increased adaptation to drought stress, nutrient deficiency, and heavy metal-containing soils. Selected Epichloë strains are utilised in agriculture mainly for their pest resistance traits, which are moderated via the production of Epichloë-derived secondary metabolites. For pastoral agriculture, the use of these endophyte infected grasses requires the balancing of protection against insect pests with reduced impacts on animal health and welfare.